Genetic polymorphism of Streptococcus mutans in Brazilian family members - Spolidorio, DMP; Hofling, J. F.; Pizzolitto, A. C.; Rosa, E. A.; Negrini, T. D.; Spolidorio, L. C. (Soc Brasileira Microbiologia, 2003)
The aim of this study was to determine whether random amplified polymorphic DNA (AP-PCR) analysis is able to differentiate genetically different Clones Of mutans streptococci, in 22 Brazilian family members. Stimulated saliva samples were collected from fathers, mothers and infants. For 5-18 months babies with erupting primary dentition, plaque samples were collected using sterile tooth pick tips. From these samples, mutans streptococci were isolated on SB-(20)agar plates. After growth, representative colonies were identified by biochemical methods on the basis of carbohydrate fermentation. Streptococcus mutans isolates were obtained from all family members and AP-PCR typed separately with a random primer (OPA-13). Bacterial cell lysates were used as template in PCR reactions and the amplified DNA fragments obtained were compared by agarose gel electrophoresis. Results demonstrated that the father shared the baby's genotype in three families and the mother shared the baby's genotype in 12 families seven babies harbored Streptococcus mutans strains similar to those of their siblings. The technique was able to demonstrate the genetic Streptococcus mutans in Brazilian family members.
Keywords: Streptococcus mutans; AP-PCR; genetic polymorphism